Factors Affecting The Company's Value Through Sustainability Reports In The Indonesia Stock Exchange - Pratiwi Dwi Karjati; Eva Winarto (Proceedings of The ICECRS, 2017)
The company's financial performance that demonstrates the success of the company is a matter of interest to the public. While the Sustainability Report is a non-financial report that is beginning to draw public attention today. This study aims to examine how the influence of financial performance on corporate value through Sustainability Report that can be used as a Reference for User Financial Statements in the decision of the right decision. The sample of this study are Companies listed in Indonesia Stock Exchange in 2015 - 2016. Independent variables in this research are Profitability Variables, Liquidity Variables, Leverage Variables measured using Financial Ratios, Mediation Variables in this study is Sustainability Report measured by using Index Disclosures derived from the Global Initiative Reporting (GRI) and Dependent Variables are Corporate Values measured using Tobins'Q. This study uses secondary data obtained at Indonesia Stock Exchange.The results of this study indicate that net profit margin, current ratio and leverage (X) have no significant effect on both sustainability reporting (Z) and the dependent variable of firm value (Y). The results of this study also proves that only the sustainability reporting (Z) Intervening variable has significant effect on the dependent variable of firm value (Y).